2023
DOI: 10.1038/s41598-023-43307-3
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of predicting maximal oxygen uptake by using the efficiency factor in healthy men

Fang Li,
Yu-Tsai Tu,
Hung-Chih Yeh
et al.

Abstract: Conventionally, efficiency is indirectly estimated through a respiratory gas analyser (oxygen, carbon dioxide), which is a complex and rather costly calculation method that is difficult to perform in many situations. Therefore, the present study proposed a modified definition of efficiency, called the efficiency factor (EF) (i.e., the ratio of work to the corresponding exercise intensity), and evaluated the relation between the EF and maximal oxygen uptake ($${\dot{\text{V}}\text{O}}_{2\max }$$ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Wier et al [ 26 ] reported that an equation for estimating VO 2 peak in the general adult population, using variables such as waist circumference, body fat percentage, and BMI, showed R values of approximately 0.80–0.82, R 2 values of 0.62 and 0.55, and an SEE of approximately 4.72–4.90. Additionally, Li et al [ 27 ] found that an equation estimated using weight, BMI, and body fat percentage in young adults had an explanatory power of 62.6% and SEE of 4.39. A recent study by Lee et al [ 15 ] estimated the VO 2 peak in male patients with SCI using age and height.…”
Section: Discussionmentioning
confidence: 99%
“…Wier et al [ 26 ] reported that an equation for estimating VO 2 peak in the general adult population, using variables such as waist circumference, body fat percentage, and BMI, showed R values of approximately 0.80–0.82, R 2 values of 0.62 and 0.55, and an SEE of approximately 4.72–4.90. Additionally, Li et al [ 27 ] found that an equation estimated using weight, BMI, and body fat percentage in young adults had an explanatory power of 62.6% and SEE of 4.39. A recent study by Lee et al [ 15 ] estimated the VO 2 peak in male patients with SCI using age and height.…”
Section: Discussionmentioning
confidence: 99%